Authentication and Access Control - Schaller, Patrick; Basin, David; Schläpfer, Michael (Applied Information Security, 2011)
Access control is the means by which access to system resources is restricted to authorized subjects. Access control has a wide scope and can be found in hardware and software, at all levels of the software stack. This includes memory management, operating systems, middleware application servers, databases and applications. In this chapter we study access control, focussing on access to remote computers, as well as access to files and other resources stored on computers.